Fast-track breeding system to introduce CTV resistance of trifoliate orange into citrus germplasm, by integrating early flowering transgenic plants with marker-assisted selection - Tomoko Endo; Hiroshi Fujii; Mitsuo Omura; Takehiko Shimada (BMC Plant Biology, 2020)
Abstract Background Global warming will expand the range of new and invasive pathogens in orchards, and subsequently increase the risk of disease epidemics and economic losses. The development of new resistant plant varieties can help to reduce the impact of pathogens, however, the breeding speed can be extremely slow, due to the growth rates of the plants, and the availability of resistance genes. Citrus trees are suffering immense damage from serious diseases such as citrus canker (XCC), huanglongbing (HLB), and citrus tristeza virus (CTV). A fast-track breeding system, that aimed at shortening the duration for disease resistance breeding by incorporating the resistance genes from related species to commercial varieties, has been developed using the integration of precocious transgenic trifoliate orange with the overexpression of CiFT and MAS. It was applied here to incorporate CTV resistance of trifoliate orange into citrus germplasm. Results One generation of backcrossed breeding, that would normally take at least 5 years, was achieved in a single year by fast-track breeding system. Linkage analysis using the corresponding DNA markers revealed that CTV resistance and T-DNA integrated regions were found in different linkage groups, and they were independently segregated in the BC progenies. The CTV resistant null segregants, in which the T-DNA integrated region was removed from their genome, were feasibly obtained by MAS in each generation of the BC progenies, and their CTV resistance was confirmed by immunological analysis. Several BC3 null segregants, whose genetic backgrounds had been substituted into citrus germplasm, except for the haplotype block of CTV resistance, were successfully obtained. CGH and NGS analyses revealed that the T-DNA integrated region was safely segregated out in null segregants. Conclusion Fast-track breeding systems are expected to shorten the required breeding time by more than one-fifth in comparison with conventional cross breeding techniques. Using this system, we obtained BC3–8, whose genetic background was successfully substituted except for the CTV resistance locus, and could be a novel mandarin breeding material. The fast-track breeding system will be useful to introduce important traits from related species to citrus germplasm while also drastically reducing the time required for breeding.